Dygai Alexander Mikhailovich - article Editorial (Бюллетень сибирской медицины)
In the article a creative biography of RAMS academician, professor A.M. Dygai, doctor of medicine, deputy director of Pharmacology Research Institute of Tomsk Scientific Center of RAMS Siberian Department has been presented.